Teachers’ Roles in Remote English Teaching at Sman 1 Blahbatuh and Sman 1 Gianyar in Gainyar Regency - Ida Ayu Made Suryaniti (STKIP AGAMA HINDU SINGARAJA, 2023)
The teacher is someone who has an important role in forming superior quality students and of course, the teacher must be able to play his role and be able to deal with various situations that exist, especially in the current situation, namely, the teacher must be able to play his role in remote teaching. So this research was made aiming to find out the role of the English teacher during remote teaching, the next aim is the academic language function used by the teacher to support their role, and the challenges faced by the teacher when playing their role in remote teaching. The location of this research is SMAN 1 Blahbatuh and SMAN 1 Gianyar in Gianyar Regency. And the research subject is the English teacher at the school. This study uses a descriptive qualitative method. Based on the results of the research and discussion, it can be concluded that teachers at SMAN 1 Blahbatuh and SMAN 1 Gianyar play eight teacher roles based on the theory by Harmer (2001) in which, there are eight roles that teachers played, namely, (1) controller, (2) organizer, (3) assessor, (4) prompter, (5) resource, (6) participant, (7) tutor, and (8) observer.